Riding the Wave of Change: Unmasking Transformative Shifts in Digital Activism for Social Justice in Indonesia - Rizky Bangun Wibisono; Sultoni Fikri (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2024)
This research delves into the transformative shifts in social media use in Indonesia, exploring how it has become more than a personal necessity, evolving into a powerful tool for civic engagement and justice advocacy. Focusing on the